(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The urgency and significance for academic institutions to apply Human Resource Management (HRM) are progressively understood and perceived, especially as Human Resource Management is capable to amplify the results from students while boosting their engagement, capability, efficiency as well as aspirations of teachers. The objective of the research is impacting the HRM culture as well as educators’ efficiency as the effectiveness of the teachers is a vital aspect of a nation’s literary and growth. Students are motivated and guided by the teachers in educational courses. As far as the unsatisfactory performance of the students is concerned, it has resulted in this objective and in turn, the research. It attempted to create a simplified hypothetical basis where the efficiency of Human Resource Management practices in academic leadership was explored to understand their effect on increasing educators’ performance.